2021
DOI: 10.1007/s10833-021-09442-2
|View full text |Cite
|
Sign up to set email alerts
|

Owning educational change in Korean schools: three driving forces behind sustainable change

Abstract: In this essay, we discuss how the COVID-19 pandemic drove key changes in schooling and what forces can sustain these changes. Responding to the argument that COVID-19-driven changes may not be sustainable, this essay offers a counter narrative from the Korean context, in which educators re-visited existing school systems and re-constructed policies and teaching practices to fill the educational vacuum caused by the pandemic. This essay specifically builds on interviews conducted with Korean educators throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…In response, research in educational leadership has examined school leaders' perceptions of and responses to bureaucratic rules, protocols, formalized evaluation and laws that are imposed by accountabilities. Findings of these studies suggest that, while school leaders perceive externally mandated rules in negative ways, they also utilize these structures and organizational routines to lead changes in schools (Datnow et al, 2020;Hubers et al, 2017;Kim, 2020a;Kim et al, 2021). In such contexts, leaders' utilization of routines is described as a critical tool to navigating tensions between accountability forces and autonomy in leading changes (Datnow et al, 2020;Hubers et al, 2017).…”
Section: Ambivalent Responses To Bureaucracymentioning
confidence: 99%
See 1 more Smart Citation
“…In response, research in educational leadership has examined school leaders' perceptions of and responses to bureaucratic rules, protocols, formalized evaluation and laws that are imposed by accountabilities. Findings of these studies suggest that, while school leaders perceive externally mandated rules in negative ways, they also utilize these structures and organizational routines to lead changes in schools (Datnow et al, 2020;Hubers et al, 2017;Kim, 2020a;Kim et al, 2021). In such contexts, leaders' utilization of routines is described as a critical tool to navigating tensions between accountability forces and autonomy in leading changes (Datnow et al, 2020;Hubers et al, 2017).…”
Section: Ambivalent Responses To Bureaucracymentioning
confidence: 99%
“…For example, enabling rules or procedures provide a set of guidelines that reflect the "best practices" and assist followers in dealing with confronting difficulties(Adler and Borys, 1996). In addition, flexibility in general rules to substitute professional judgment can enable than hinder finding solutions(Kim et al, 2021;Sinden et al, 2004;Wu et al, 2013). Therefore, these enabling functions can support educators' motivation to learn, job satisfaction and organizational learning.…”
mentioning
confidence: 99%
“…Numerous studies have reported that crisis-informed schooling has catalyzed educational leaders to reimagine the conventional school practices. For instance, Kim et al's (2021a) study with policy actors in South Korea (hereafter Korea) suggested that the pandemic forced policy elites and school administrators to think creatively to replace the old grammar of Korean schools-bureaucratic, competition-oriented and adult-centered-with a new grammar of schooling, focused on professional and democratic culture, equity-minded teaching and student-centered personalized learning. Similarly, McLeod and Dulsky's (2021) study on leaders in the United States and China during the early stages of the pandemic highlighted "unexpected positive outcomes," such as challenging the status quo, leveraging technology to enhance teaching and recognizing the power of community (p. 10).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that crisis-informed schooling has catalyzed educational leaders to reimagine the conventional school practices. For instance, Kim et al. ’s (2021a) study with policy actors in South Korea (hereafter Korea) suggested that the pandemic forced policy elites and school administrators to think creatively to replace the old grammar of Korean schools—bureaucratic, competition-oriented and adult-centered—with a new grammar of schooling, focused on professional and democratic culture, equity-minded teaching and student-centered personalized learning.…”
Section: Introductionmentioning
confidence: 99%
“…ESTUDIOS SOBRE EDUCACIÓN / 2022 INTRODUCCIÓN E l término "innovación educativa" se refi ere fundamentalmente a los procesos de cambio que se dan 'a pie de aula' en los centros educativos y que buscan mejorar la práctica educativa. Sin refl exionar muchas veces sobre la dirección en la que se orienta la innovación, el mero uso de nuevas metodologías en el aula escolar se considera causa de motivación tanto para los docentes como para el alumnado (Fix et al, 2019), en especial si estas metodologías incluyen el uso de tecnologías digitales (Kim et al, 2021). Aunque originariamente fueron las universidades las promotoras de dichos cambios, se ha observado que no es fácil adaptar las formas de innovación promovidas desde las universidades a la realidad contextual de los centros educativos (Pareja Roblin y McKenney, 2019), lo que ha dado lugar a un giro en la investigación educativa.…”
unclassified